Goat systems of Eastern Andalusia (Spain): Characterization and classification - Ruíz F.A.; Sayadi S.; Calatrava J. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
Andalusia is the region with the largest goat population in Spain and Europe. In this region the most common goat breeding is based on the Murciano-Granadina race, located mainly in the Eastern mountainous areas. Different productive models and managerial schemes are found in the area, going from very extensive for meat production to the very technical and specialised system for intensive dairy production. The aim of this study is to perform a goat farming system typology of Eastern Andalusia. Based on data gathered from a survey of 151 farmers, a multivariate statistical analysis has been performed to identify different models of goat production in the area. As a result of a Principal Component (PC) analysis, 71.6 percent variance was explained. Three components have been estimated. The first component -size- included total surface area and number of goats. The second -land use and sheep- is formed by the proportion of cultivated area and presence of sheep. The third -milk productivity- included milk sold per goat. After conducting a cluster analysis based on these three principal components, farms were classified into four groups. Group 1 is the largest group, with the smallest flocks and smallest area. Group 2 with smaller farms had a high proportion of crop surface area. Group 3 was made up of farms which had large surface areas and big flocks. Group 4 was made up of farms where the presence of sheep is important.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)